Edutainment with the Help of Volcanic Media for the Development of Children's Language in Group B at TK X Kamal, Bangkalan - Adhani, Dwi Nurhayati; Shofiyah, Ainin (Proceedings International Conference on Sustainable Innovation (ICoSI), 2022)
This study aims to look at the development oflanguage owned by group B children in TK X Kamal,Bangkalan using edutainment. On the implementation ofusing mountain media erupted by performing a volcaniceruption process simulation. Learning about volcaniceruptions is expected to enable children to get to know theenvironment, and explain the symptoms of nature. Thisstudy uses quantitative descriptive research to determine thenumber of students who can describe the process of eruptingthe mountain verbally. The location of this study wasconducted at TK X kamal Bangkalan with a total of 16students. The results of this study were to look at thelanguage development of children in group B in explainingnatural phenomena such as volcanic eruptions